Self-Assessment of Symptoms by the Patient with Cancer: the Time is Now - Pires, Ana Maria Teixeira (2022)
The article describes concepts and evidences based on scientific literature and opinions of professionals who work with cancer patients through a self-report instrument for signs and symptoms. PRO-CTCAE® is an instrument utilized for cancer patients care with the objective of empowering the patient in decision-making regarding the planning and monitoring of their treatment, highlighting symptoms hitherto not questioned or valued, qualifying patient and health professionals communication, reflecting global strategies goals for chronic diseases control.